THE EFFECT OF ENERGY CONSUMPTION ON GROSS DOMESTIC PRODUCT (GDP) - Otrinawa, Agung; Devi Valeriani; Aja Nasrun (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2025)
This study aims to determine the effect of oil, natural gas, and coal consumption on Indonesian domestic product. The research uses descriptive analysis techniques and quantitative analysis, namely multiple linear regression methods. The scope of the data used in this study is the time series data of Indonesia's gross domestic product from 1999 to 2023. The results showed that oil and natural gas consumption both had a positive and insignificant effect on gross domestic product while coal consumption had a positive and significant effect on gross domestic product.